Generation Z Job Preferences in the MSME Sector: An Analysis of Herzberg's Hygiene-Motivator Factors with Compensation as a Mediating Variable in Gorontalo Province - Syamsul B. Biki; Andi Yusniar Mendo; Mentari Rizki Sawitri Pilomonu; Mohammad Dimas Suronoto (IJIP : Indonesian Journal of Islamic Psychology, 2026)
This study aims to analyze the factors influencing young job seekers' preferences in the MSME sector of Gorontalo Province, specifically examining the role of work environment, work flexibility, and compensation. A quantitative approach with a descriptive-correlational design was employed, involving 189 Generation Z respondents aged 18-28 years who reside in Gorontalo Province and have intentions or are currently seeking employment in the MSME sector. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that work environment and compensation significantly influence job seeker preferences, while work flexibility does not have a direct significant effect. However, work flexibility influences job preferences indirectly through compensation as a mediating variable. Of the seven hypotheses tested, six were accepted, and one was rejected. The study concludes that compensation and work environment are primary factors attracting Gen Z to the MSME sector, whereas flexibility offerings require adequate compensation to be effective. These findings reinforce Herzberg's Two-Factor Theory and provide practical implications for MSME stakeholders in developing strategies to attract young talent.